PENGARUH METODE PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR LARI CEPAT - Warti Manalu (Jurnal Pedagogik Olahraga, 2017)
Abstract :The aim of this study is to determine the difference between learning by games method and learning by drills method including the students’ learning motivation on sprint running result. The research was conducted to grade five students of Santa Maria Elementary School in Jakarta. The research took treatment by level 2 x 2. The total numbers of research population were 54 whereas the samples were 11 students. The data was analysed by 2 parallel varians (ANAVA) and was tested by Turkey test on significant level of α = 0,05. The final conclusions for the research showed (1) Scores of sprint running using learning by games methodology (A1) were lower than the other ones using learning by drills methodology (A2) in Santa Maria Elementary School Jakarta. (2) There was an interaction between learning methodology (A) and learning motivation (B) to result of sprint running in Santa Maria Elementary School Jakarta. (3) The score of learning by games methodology with high motivation (A1B1) was lower than the score of learning by drills with high motivation (A2B1) in Santa Maria Elementary School Jakarta. The scores of sprint running in treatment of learning by games with high motivation (A1B2) were higher than the scores of learning by drills  with low motivation (A2B2) in Santa Maria Elementary School Jakarta. . Key Words : learning by games methodology and learning by drills methodology, learning motivation on sprint running. Abstrak : Tujuan dari penelitian ini adalah untuk mengetahui perbedaan antara metode pembelajaran bermain dan metode pembelajaran latihan dan  motivasi belajar siswa terhadap hasil belajar lari cepat. Penelitian ini dilakukan pada siswa kelas V SD Santa Maria Jakarta. Penelitian ini menggunakan treatment by level 2 x 2. Populasi dalam penelitian ini terdiri dari 82 dan menggunakan sampe 44 siswa. Teknik analisa data adalah analisis varians dua jalur (ANAVA) dan dilanjutkan dengan uji Turkey pada tingkat signifikan α = 0,05. Hasil penelitian ini menunjukkan bahwa (1) nilai hasil belajar lari cepat pada perlakukan metode pembelajaran bermain  (A1) lebih rendah dari nilai metode latihan  (A2) di SD Santa Maria Jakarta (2). Terdapat interaksi antara metode bermain (A)  dan motivasi belajar (B) terhadap hasil belajar lari cepat di SD Santa Maria Jakarta (3). Nilai hasil belajar pada perlakuan metode latihan motivasi belajar (A1B1) lebih tinggi dari nilai metode bermain percaya diri tinggi (A2B1) di SD Santa Maria Jakarta. Nilai hasil belajar lari cepat pada perlakukan metode bermain percaya diri rendah (A1B2) lebih rendah dari pendekatan bermain percaya diri rendah (A2B2) di SD Santa Maria Jakarta.Catat kunci : metode bermain dan metode latihan, motivasi belajar pada lari cepat.